Optimizing the process efficiency of atomic layer deposition of alumina for its sustainability improvement: a combined experimental and modeling study. (1st October 2016) - Xie, Yuanyuan; Pan, Dongqing; Ma, Lulu; Yuan, Chris
Abstract: Atomic Layer Deposition (ALD) technology has been under rapid development toward a broad array of applications, while the low deposition efficiency and heavy waste of TMA are limiting its industrial-scale applications. In this paper, a mathematical model is developed based on an experimental ALD of alumina process, and an optimization approach is then proposed to investigate the optimal ALD operating for the minimum TMA wastes and the maximum Al2 O3 production under various conditions. Results show that the maximum TMA adsorption and alumina production cannot be achieved simultaneously, but sufficient H2 O dosing can minimize the gap between them. The influence of substrate surface saturation condition and operating temperature is also investigated. Results quantitatively show that lower surface saturation condition requires more ALD cycles to improve the precursors' utilization efficiency, while the optimal ALD process can increase the maximum alumina production from2.7 × 10 −4  mol/m 2 to 7.5 × 10 −4  mol/m 2 with the temperature rise from 150 °C to 200 °C. Besides, it is found that the maximum production of both |-Al(CH3 )2 and alumina is influenced by their corresponding half-cycle duration, and sufficient treatment time can significantly improve the ALD process efficiency and reduce the total TMA waste. These insights into the minimum TMA waste and maximum production of surface products can guide the future design of ALD of alumina process with better efficiency and sustainability. Highlights: A combined experimental and modeling work is conducted on the ALD of alumina process. The detailed surface chemistry is considered, and is validated by the experimental results. An optimization approach is developed to explore the optimal ALD of alumina process. The effect of different ALD operating parameters are investigated by both modeling and experiment.